Prevalence, patterns, and correlates of equestrian injuries in Malaysia: A cross-sectional study - Nizar A Majeedkutty; Nor A.B. Khairulanuar (Wolters Kluwer Medknow Publications, 2017)
Background: Equestrian sport carries with it an implicit risk of injury. Despite the frequency of injuries in equestrian sports, there is no published study on injuries of equestrian athletes in Malaysia. Objective: The objective of this study was to determine the prevalence of injuries and its correlates among horseback riders. Subjects And Methods: A web-based standardized questionnaire was used to collect data for this cross-sectional survey. Horseback riders aged 18 years and above were included in the study. Out of 169 participants, 93 were females and 76 were males. The correlation of injuries to gender, age, level of experience, exercise habits, use of safety measures, and type of equestrian sport were determined. Chi-square test was performed to test for statistical significance. Results: The prevalence was high with 85.8% of the participants reporting symptoms and characteristics of injuries in the past 12 months. The most frequently perceived symptoms reported were in the upper extremities (43.4%) followed by lower extremities (40.7%), head injury (8.3%) and injuries of upper and lower back (3.4%). There was a higher prevalence of injury among female participants (55.03%) than males (42.60%). A significant correlation was found between gender and prevalence of injuries. About 70% of the riders sustained soft tissue injuries. Fifty-five percent of the injured were involved in recreational riding. The most common mechanism of injury was a fall from a horse. Sixty percent of the injured riders did not seek medical attention after being injured, and physiotherapy consultation was even lower with 10.3%. Conclusions: The high prevalence of injuries and low rate of medical consultation emphasize the need for education programs on safety in Malaysia. Sessions should be held to improve coaching for riders and instructors, and their knowledge of the nature of the horse, mechanisms of injuries, horse handling, and riding skills to help them host safe equestrian activities.